Better IVF/ICSI success rates with metformin use in women with polycystic ovary - Vargas Tominaga, Luis (2015)
Objectives: To determine metformin influence in in vitro fertilization (IVF) and intracytoplasmatic sperm injection (ICSI) success rates in women with polycystic ovaries (PCO). Design: Retrospective study. Setting: Fertility and Gynecology Southern Center, Cusco, Peru. Participants: Women with polycystic ovaries  associated infertility. Methods: We compared IVF/ICSI success rates in 7 women with diagnosis of PCO who  used metformin and 9 women with PCO who did not use metformin. Main outcomes measures: Pregnancy. Results:  In PCO women using metformin implantation rate was 35%, biochemical pregnancy rate 71,4%, and clinical pregnancy rate 57,1%. In PCO women not using metformin, success rates were respectively 0%, 11,1%, and 0%. Conclusions: Metformin use improved IVF/ICSI success rates in PCO women.